PENGARUH KETEBALAN IRISAN KERUPUK SAGU TERHADAP WAKTU PENGERINGAN DAN DAYA KEMBANG KERUPUK - Mergina Miro; Yus Witdarko; Yosehi Mekiew (Musamus AE Featuring Journal, 2022)
This study aimed to determine the effect of the thickness of the sago cracker slices on the drying time and the ability to swell the crackers in the frying process. The research was started by making sago cracker dough and then sliced ​​with a thickness of 3 mm, 5 mm, and 7 mm. Each slice was then dried in the sun for 27 hours (3 days). The sampling of cracker chips was measured for water content at the 9th hour, 18th hour, and 27th hour. Cracker chips are fried to test their ability to swell. The results showed that the drying time for the thickness of the 3 mm sago cracker slices was the fastest compared to the 5 mm and 7 mm thickness of the sago cracker slices. The thickness of the 3 mm sago cracker slices also has the highest ability to swell compared to the 5 mm and 7 mm thicknesses of the sago cracker slices.